A Basic Post-SET Extension of NSDs Is Essential for Nucleosome Binding In Vitro. (July 2014) - Allali-Hassani, Abdellah; Kuznetsova, Ekaterina; Hajian, Taraneh; Wu, Hong; Dombrovski, Ludmila; Li, Yanjun; Gräslund, Susanne; Arrowsmith, Cheryl H.; Schapira, Matthieu; Vedadi, Masoud
The nuclear receptor SET domain-containing family of proteins (NSD1, NSD2, and NSD3) is known to mono- and dimethylate lysine 36 of histone H3 (H3K36). Overexpression and translocation of NSDs have been widely implicated in a variety of diseases including cancers. Although the substrate specificity of NSDs has been a subject of many valuable studies, the activity of these proteins has never been fully characterized in vitro. In this study, we present full kinetic characterization of NSD1, NSD2, and NSD3 and provide robust in vitro assays suitable for screening these proteins in a 384-well format using nucleosome as a substrate. Through monitoring the changes in substrate specificity of a series of NSD constructs and using molecular modeling, we show that a basic post-SET extension common to all three NSDs (corresponding to residues 1209 to 1226 of NSD2) is essential for proper positioning on nucleosome substrates.